Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1136/fn.75.3.f197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexamethasone on IL-2 and IL-3 production by mononuclear cells in neonates and adults.

Abstract: The effect of dexamethasone on interleukin 2 (IL-2) and interleukin 3 (IL-3) production by mononuclear cells in preterm and term infants and adults was evaluated. The capacity of mononuclear cells to produce these cytokines, in preterm infants with bronchopuhmonary dysplasia (BPD) and treated with dexamethasone, was compared with that before treatment.Twenty six preterm and 36 term neonates and 24 healthy adults were included in the study. Mononuclear cells isolated from neonatal cord blood (CBMC) and adult pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
5
11
0
Order By: Relevance
“…In addition, CBMC have a unique cytokine profile when compared to PBMC. In accordance with our results, previous studies have demonstrated that blood MC or purified T cells from neonates are more sensitive to dexamethasone than cells from adults with regard to proliferation, IL-2 receptor expression [14], or IL-2 and IL-3 production [15]. Moreover, addition of dexamethasone to CBMC from preterm and term newborns at pharmacological doses induced maximal and moderate suppression of IL-2 and IL-3 production, respectively, whereas PBMC of adults were less affected [15].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, CBMC have a unique cytokine profile when compared to PBMC. In accordance with our results, previous studies have demonstrated that blood MC or purified T cells from neonates are more sensitive to dexamethasone than cells from adults with regard to proliferation, IL-2 receptor expression [14], or IL-2 and IL-3 production [15]. Moreover, addition of dexamethasone to CBMC from preterm and term newborns at pharmacological doses induced maximal and moderate suppression of IL-2 and IL-3 production, respectively, whereas PBMC of adults were less affected [15].…”
Section: Discussionsupporting
confidence: 81%
“…In accordance with our results, previous studies have demonstrated that blood MC or purified T cells from neonates are more sensitive to dexamethasone than cells from adults with regard to proliferation, IL-2 receptor expression [14], or IL-2 and IL-3 production [15]. Moreover, addition of dexamethasone to CBMC from preterm and term newborns at pharmacological doses induced maximal and moderate suppression of IL-2 and IL-3 production, respectively, whereas PBMC of adults were less affected [15]. The current observation that PBMC incubated with a low concentration of dexamethasone (10 -7 M) responded in enhanced spontaneous secretion of IL-1ß and IL-6, whereas neonatal cells were not affected, is of interest, supporting the existence of differences between CBMC and PBMC.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is shown in the present work that CBMC from preterm newborns differ from PBMC of adults in their sensitivity to the in vitro effect of IM and IB on IL-1ra production. These findings are supported by previous reports indicating that neonatal MC differ from those of the adult in cytokine profile, sensitivity to the inhibitory effect of dexamethasone and NSAIDs on the proliferative response, and cytokine production [13,14,[22][23][24][25][26][27]. It is possible that the variance in the response to NSAIDs between CBMC of preterms and PBMC of adults may be related to different levels of COX in the cells of the 2 age groups.…”
Section: Discussionsupporting
confidence: 79%
“…Research on neonatal mononuclear cells, and particularly those of preterm newborns, has demonstrated that they are more sensitive to the inhibitory effect of DEX as for their proliferative response [21], and the production of IL-2, IL-3 [22], IL-6 and TNF-· induced by mitogens [23]. On the other hand, they are less sensitive to the effect of the drug on the spontaneous secretion of IL-1ß or IL-6 as compared to adult cells [23].…”
Section: Introductionmentioning
confidence: 99%